Pillar depicting images of apsaras and female deities - Temples of India Project Team (Jio Institute, 2024)
The pillars in the mandapa of the Harshnath Temple lack homogeneity, suggesting they may have been replaced at a later date. One of these pillars is enriched with beautiful images of apsaras and female deities like Parvati, as seen in this image, situated within the niches of the pillar. Under these pillar niches are panels depicting musicians, dancers, celestial beings, deities like Ganesha and ascetics. The four-armed Goddess depicted here appears to be Goddess Bhairavi. She holds a staff crowned with a skull and an attribute resembling a mace in her right hand. The left arm above is broken and the lower one is placed near her vahana, a dog. The panel below depicts dancers and musicians.